2012
DOI: 10.4049/jimmunol.1200880
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Clr-g, a Ligand for NK Cell Activation Receptor NKR-P1F: Crystal Structure and Biophysical Properties

Abstract: Interactions between C-type lectin-like NK cell receptors and their protein ligands form one of the key recognition mechanisms of the innate immune system that is involved in the elimination of cells that have been malignantly transformed, virally infected, or stressed by chemotherapy or other factors. We determined an x-ray structure for the extracellular domain of mouse C-type lectin related (Clr) protein g, a ligand for the activation receptor NKR-P1F. Clr-g forms dimers in the crystal structure resembling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…S5A). The mode of KACL dimerization resembles that of CD69 (34), Clrg (29), and certain Ly49s (22,23,37): Following superposition of the KACL and CD69 dimers through one of their subunits, the orientation of the other subunits differed by only an 8°rotation (23°for KACL superposed onto Clrg; 20°for KACL superposed onto Ly49L). As in the case of CD69 and other C-type lectin family dimers, the N termini of the KACL CTLDs point in the same direction (i.e., toward the cell membrane) (Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…S5A). The mode of KACL dimerization resembles that of CD69 (34), Clrg (29), and certain Ly49s (22,23,37): Following superposition of the KACL and CD69 dimers through one of their subunits, the orientation of the other subunits differed by only an 8°rotation (23°for KACL superposed onto Clrg; 20°for KACL superposed onto Ly49L). As in the case of CD69 and other C-type lectin family dimers, the N termini of the KACL CTLDs point in the same direction (i.e., toward the cell membrane) (Fig.…”
mentioning
confidence: 96%
“…In addition, we determined the structure of killer cell lectin-like receptor G1 (KLRG1) bound to E-cadherin, a non-MHC ligand that is down-regulated in metastatic tumors (27). By contrast, no structural information is available for any of the NKC-encoded receptor-ligand pairs identified to date (Nkrp1f-Clrg and Nkrp1d-Clrb in rodents and NKRP1A-LLT1, NKp80-AICL, and NKp65-KACL in humans), except for the structures of mouse Nkrp1a and Clrg in unbound form (28,29). To understand genetically linked recognition by C-type lectin-like receptors in the NKC at the atomic level, we determined the structure of NKp65 in complex with its keratinocyte ligand KACL.…”
mentioning
confidence: 99%
“…The structures of NKRP1 members were reported for human CD69, the mouse Clr-G proteins ([Protein Data Bank] PDB ID: 3RS1) [24] and mouse Nkrp1a (PDB IDs: 3M9Z and 3T3A) [25,26]. Their ectodomains adopt the C-type lectin fold, composed of two α-helices and two antiparallel β-sheets [27].…”
Section: Introductionmentioning
confidence: 99%
“…LLT1 and AICL bind their ligands, NKRP1A and NKp80, respectively, with low affinity (LLT1-NKRP1A: Kdß50 μM [23], AICL-NKp80: Kdß4 μM [14]), whereas NKp65 binds to KACL with significantly higher affinity (Kdß0.01 μM) [15]. Since these differences are strongly correlated with the recognition mechanisms, further structural studies at atomic resolution will be required for their clarification.The structures of NKRP1 members were reported for human CD69, the mouse Clr-G proteins ([Protein Data Bank] PDB ID: 3RS1) [24] and mouse Nkrp1a (PDB IDs: 3M9Z and 3T3A) [25,26]. Their ectodomains adopt the C-type lectin fold, composed of two α-helices and two antiparallel β-sheets [27].…”
mentioning
confidence: 99%
“…However, these results were not confirmed upon independent re-examination [7]. Moreover, it was demonstrated that NKR-P1 receptor family possess structural motifs optimized for the protein-protein, but not saccharide-protein interactions and protein ligands for some of them were identified [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 94%